2020
DOI: 10.1186/s12957-020-01967-9
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes for transvaginal specimen extraction versus minilaparotomy after robotic anterior resection for colorectal cancer: a mono-institution retrospective study

Abstract: Background: Colorectal cancer resection surgery with transvaginal specimen extraction is becoming increasingly accepted and used by surgeons. However, few publications on robotic anterior sigmoid colon and rectal cancer resection with transvaginal specimen extraction (TVSE) have been reported, and a clinical outcome comparison between conventional robotic minilaparotomy (LAP) and transvaginal specimen extraction in anterior sigmoid colon and rectal cancer resection has not been performed. The current study com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…But some scholars believe that transvaginal NOSES may cause problems with tumor implantation or wound infection, one meta-analysis concluded that there was no significant difference in oncological outcomes between the NOSES group and the traditional abdominal incision group [9]. Similar results were obtained by Gao et al [10] who showed no significant difference in 3-year overall survival and disease-free survival between the two groups. In our study, patients did not experience tumor recurrence, implant metastasis within the follow-up date, and also did not experience infection problems in their perioperative wounds, which were more desirable than those of conventional surgery.…”
Section: Discussionmentioning
confidence: 54%
“…But some scholars believe that transvaginal NOSES may cause problems with tumor implantation or wound infection, one meta-analysis concluded that there was no significant difference in oncological outcomes between the NOSES group and the traditional abdominal incision group [9]. Similar results were obtained by Gao et al [10] who showed no significant difference in 3-year overall survival and disease-free survival between the two groups. In our study, patients did not experience tumor recurrence, implant metastasis within the follow-up date, and also did not experience infection problems in their perioperative wounds, which were more desirable than those of conventional surgery.…”
Section: Discussionmentioning
confidence: 54%
“…A systematic review concluded that there was no significant difference in oncologic outcomes between NOSE and abdominal incision groups [ 9 ]. One study reported similar overall survival and disease-free survival between the two approaches, and another study reported no tumor implantation problems during the follow-up period after the NOSE procedure [ 10 , 11 ]. The use of a protective bag before specimen extraction would reduce the risk of cancer cell implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies[ 5 , 7 , 8 , 17 ] have confirmed the safety and feasibility of robotic NOSES surgery as a minimally invasive procedure, enhancing surgical quality and expediting postoperative recovery. Robotic resection using the NOSES I-type F method (R-NOSES I-F) represents a novel approach characterized by intussusception to achieve transanal specimen eversion.…”
Section: Introductionmentioning
confidence: 83%